2018
DOI: 10.1002/anie.201809551
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Aza‐Mislow–Evans Rearrangement of N‐Acyl tert‐Butanesulfinamides into α‐Sulfenyloxy Carboxamides

Abstract: Ad iastereoselective [2,3] rearrangement of O-silyl N-sulfinyl N,O-ketene acetals derived from chiral N-acyl tertbutanesulfinamides was developed, giving a-sulfenyloxy carboxamides with excellent enantioselectivity.E nolization and subsequent silylation of N-acyl tert-butanesulfinamides initiate this aza variant of the Mislow-Evans rearrangement, in which the chirality at the sulfur atom in the rearrangement precursors is faithfully transferred to the a-carbon stereocenter of the products.T he Ellman sulfinami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Lastly, in 2018, Lu and co-workers proposed an aza variant of the Mislow-Evans rearrangement (Table 17). 98 This transformation capitalized on in situ formation of Nsulfinyl ketene N,O-acetals from N-acyl sulfinamides 88aza and provided access to versatile, carboxamide building blocks 89a-za with excellent diastereoselectivity. Furthermore, the importance of the ketene moiety was confirmed in a control experiment as, in the absence of silylation, no product formation was observed.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Lastly, in 2018, Lu and co-workers proposed an aza variant of the Mislow-Evans rearrangement (Table 17). 98 This transformation capitalized on in situ formation of Nsulfinyl ketene N,O-acetals from N-acyl sulfinamides 88aza and provided access to versatile, carboxamide building blocks 89a-za with excellent diastereoselectivity. Furthermore, the importance of the ketene moiety was confirmed in a control experiment as, in the absence of silylation, no product formation was observed.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…The rearrangement of allylic sulfoxides to allylic sulfenate esters is a popular example of [2,3]sigmatropic rearrangements. [1][2][3] This type of reaction is also known as Mislow-Evans rearrangement [4][5][6][7][8][9][10][11] and is widely used in asymmetric synthesis due to the possibility of chirality transfer from the carbon bearing the sulfoxide group to the alcohol resulting from a subsequent reaction with an appropriate thiophile (Figure 1A).…”
mentioning
confidence: 99%
“…The rearrangement of allylic sulfoxides to allylic sulfenate esters is a popular example of [2,3]sigmatropic rearrangements. [1][2][3] This type of reaction is also known as Mislow-Evans rearrangement [4][5][6][7][8][9][10][11] and is widely used in asymmetric synthesis due to the possibility of chirality transfer from the carbon bearing the sulfoxide group to the alcohol resulting from a subsequent reaction with an appropriate thiophile (Figure 1A). Hence, the Mislow-Evans rearrangement is a popular tool in the synthesis of bioactive substances and natural products like terpenes, [12] vernolepin, [13,14] amphidinol 3, [15] and pyrenolide D. [16] The transition state of the Mislow-Evans rearrangement has attracted considerable attention, because it determines the stereochemistry of the reaction.…”
mentioning
confidence: 99%
“…Our previous studies demonstrated highly stereoselective [2,3]-sigmatropic rearrangement of O-silyl N-tert-butanesulfin- In this rearrangement, chiral information was transferred from the sulfur atom in the sulfinyl group to the α-position in the amide products. 16 Consequently, Ellman's tert-butanesulfinamide, 17 commonly used as a chiral ammonia equivalent, works well as a latent chiral hydroxyl group. We envisaged that aza-Mislow−Evans rearrangement 18 could lead to O,N-bifunctionalization of disubstituted ketenes: addition of lithiated N-substituted tert-butanesulfinamides to disubstituted ketenes, followed by silylation, might give fully substituted O-silylated enolates, which in turn might undergo rearrangement to give tertiary α-sulfenyloxy carboxamides (Scheme 1c).…”
mentioning
confidence: 99%